PENYELESAIAN SENGKETA PENGALIHAN SAHAM PERUSAHAAN PEMBANGKIT LISTRIK ENERGI PANAS BUMI MELALUI PUTUSAN ARBITRASE ASING (SIAC) - I Gusti Agung Ayu Gita Pritayanti Dinar (University of Udayana, 2015)
Arbitration is one of popular means to solve disputes arise between parties in international business nowadays. Arbitration characteristics such as: confidentiality; “party autonomy” (principle which gives both parties freedom to agree on arbitration institution or ad hoc arbitration, to appoint an arbitrator, arbitration procedure, place of arbitration, governing law) and also international enforceability due to the New York Convention 1958 are regarded as part of the main advantages of arbitration. This research is a normative law using concept analysis approach legal, regulatory approaches undertaken by examining legislation relevant to the issues of law and experiences to approach a case of transfer of shares Bali Power Corporate. Sources of legal materials used in this study are such as related literature, journals, articles and thesis that are relevant to the subject matter. The results of this study indicate that partial award (SIAC) has a binding force for the parties to the dispute. Legal implications arising from this decision that the party whose breach the contract has an obligation to replace the damage of PT. Bali Tenaga Corporate since the contract was signed.